Russell-names: an introduction to Millian descriptivism - Predelli, Stefano (Springer, 2016)
This essay studies the semantic properties of what I call Russell-names. Russell-names bear intimate semantic relations with descriptive conditions, in consonance with the main tenets of descriptivism. Yet, they are endowed with the semantic properties attributed to ordinary proper names by Millianism: they are rigid and non-indexical devices of direct reference. This is not an essay in natural language semantics, and remains deliberately neutral with respect to the question whether any among the expressions we ordinarily classify as proper names behave as Russell-names. Its aim is rather that of casting a new light on the traditional debate about descriptivism on the one hand, and, on the other, what is commonly understood as a radically anti-descriptivist approach. From the viewpoint of descriptivism, the conceivability of Russell-names provides welcome relief from the pressure exerted by considerations at odds with a flaccid and/or indexical treatment of proper names. Conversely, from a Millian standpoint, the conceivability of Russell-names indicates that the Millian stance, far from providing a meagre picture of names as ‘mere tags’, is at least in principle consistent with the recognition of their semantic bonds with richer descriptive material. The Appendix provides a formal treatment of Russell-names within a model theoretic semantics for indexical intensional languages, developed within an original ‘double-context’ framework.